Apoptosis as a Determinant of Atherothrombosis - Tedgui, Alain; Mallat, Ziad (Thrombosis and Haemostasis, 2001)
Clinical manifestations of atherosclerosis are the consequences of atherosclerotic plaque rupture that triggers thrombus formation. Tissue factor (TF) is a key element in the initiation of the coagulation cascade and is crucial in thrombus formation following plaque disruption. TF activity is highly dependent on the presence of phosphatidylserine (PS), an anionic phospholipid that is redistributed on the cell surface during apoptotic death conferring a potent procoagulant activity to the apoptotic cell. Apoptosis occurs in the human atherosclerotic plaque and shed membrane apoptotic microparticles rich in PS are produced in considerable amounts within the lipid core. These microparticles carry almost all TF activity and are responsible for the procoagulant activity of the plaque. Moreover, luminal endothelial cell apoptosis might be responsible for thrombus formation on eroded plaques without rupture. Apoptosis might also play a major role in blood thrombogenicity via circulating procoagulant microparticles that are found at high levels in patients with acute coronary syndromes.
Keywords: Atherosclerosis; plaque stability; apoptosis; tissue factor; phosphatidylserine